Сorrectness of a managerial decision and competence of small business managers - Джулакидзе, Е.; Барбакадзе, Е. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2018)
To make a decision means to analyze all the possible alternatives of goal achievement, and identification of them in the appropriate situation, and to construct a full action plan taking into account all new opportunities and threats. In addition, in the process of managing the organization contradictions occur between goals and situations, the correct solution of which determines the need to change the course of the manager's action to achieve the desired goal. This fact is stipulated by many reasons, among which can be distinguished: the global nature of competition, the intensive expansion of product mix, rapid technology upgrade, reduced product life cycle (service), production of combined products and increased consumer orientation. At the same time, all decisions can be considered as an integral act limited by economic, organizational, technological, legal, social, political, psychological and information constraints. In order to develop a legitimate solution, it is necessary to adequately consider the objective components of the solution: purpose, situation, problems, limitations, opportunity, alternative, motive, risk. With this view knowledge, capabilities, skills, experience of the manager, his professional qualities are o0f great importance. .According to the data obtained from a survey conducted to find out how small business managers have the opportunity to make successful decisions, it should be noted that at present time, the problem of small business development is more of a «management deficit»  than a «lack of financial resources». However, at the same time, it should be noted that the future generation feels more strongly and better the need for skilled knowledge in the decision-making process.